2020
DOI: 10.3390/jcm9061632
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Comorbidity of Atopic Dermatitis in Children: A Large-Scale Population Study Based on Real-World Data

Abstract: This study aimed at exploring atopic dermatitis (AD) prevalence in children and exhaustively analyzing their comorbidity. We conducted a descriptive analysis of their socio-demographic and comorbidity characteristics in the EpiChron Cohort (Aragón, Spain). Adjusted odds ratios (OR) were calculated for each comorbidity using logistic regression models. In total, 33,591 children had a diagnosis of AD, resulting in an overall prevalence of 15.5%. AD prevalence was higher in girls compared to boys, in 3–9-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
4
35
0
2
Order By: Relevance
“…Another relevant comorbidity in this cluster was anxiety and neuroses, and sensory-processing disorders (hearing loss in women and visual impairment in men). Further studies are needed to research the relationship between these associations, especially in the case of sensory-processing disorders, congenital anomalies and some musculoskeletal diseases in which there are very few studies reporting them 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant comorbidity in this cluster was anxiety and neuroses, and sensory-processing disorders (hearing loss in women and visual impairment in men). Further studies are needed to research the relationship between these associations, especially in the case of sensory-processing disorders, congenital anomalies and some musculoskeletal diseases in which there are very few studies reporting them 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, atopic diseases have been reported to be associated with functional GI disorders such as functional dyspepsia and irritable bowel syndrome [ 15 ]. Moreover, adults with AD had higher odds of developing gastroenteritis than those without AD [ 33 , 34 ]. In this study, we found the GI function such as dyspepsia and gastric discomfort correlated with AD symptoms (SCORAD).…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis (AD) develops after inflammatory responses against common environmental antigens (Ag) and is a lifelong disease with approximately 10 to 15% prevalence in both children and dogs [ 1 , 2 ]. Pruritus, the hallmark symptom of AD, causes a substantial impact on the quality of life for the dog patients, as well as the dog owners, and affected humans ([ 3 , 4 ] and references therein).…”
Section: Introductionmentioning
confidence: 99%